Detection of Diseases Caused By Obesity Using Certainty Factor Method - Sri Widodo; Yeni Tri Utami; Indra Hastuti (Proceeding of International Conference on Science, Health, And Technology, 2019)
Obesity is overweight as a result of excessive body fat accumulation. Everyone needs some body fat to store energy, as a heat insulator, a barrier to organ shocks and other functions. Many diseases can be associated with obesity, such as diabetes, high blood pressure, coronary heart disease, stroke, and even some cancers. Lack of knowledge and concern for nutritional balance in the body and difficulty monitoring weight development are causes of obesity. The purpose of this research is to develop an application to detect diseases due to obesity using the Certainty Factor method based on perceived symptoms. The system will display amount of confidence in symptoms of the possibility of illness due to obesity suffered. The amount of the trust value is result of calculations using Certainty Factor (CF) method. Knowledge representation used in this study is production rule. The inference method used to get conclusion is forward chaining.